2015
DOI: 10.2147/plmi.s64383
|View full text |Cite
|
Sign up to set email alerts
|

BRAF mutational analysis in ovarian tumors: recent perspectives

Abstract: BRAF mutations are rare in ovarian cancer and mainly occur in indolent serous borderline tumors (SBTs), also known as serous tumors of low malignant potential or atypical proliferative serous tumors. The reported percentage of BRAF mutations in SBTs varies from 23% to 71%. Although a high percentage of stage II-IV SBTs with noninvasive implants have progressed to invasive low-grade serous carcinomas when patients were observed for 5 years or longer, BRAF mutations are rare in low-grade serous carcinomas as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…( Previous reports from other countries have shown that MOC has a lower frequency of BRAF mutation (2-20%). [1,2,6] Our data revealed that the BRAF missense mutation rate is relatively up to 80% (n = 16/20) using the FemtoPath BRAF Mutation Screen Kit. This kit is a PCR-based test using proprietary primers which can selectively amplify the somatic mutations in activating segment of the BRAF gene, and suppresses the ampli cation of wild-type BRAF gene in human genomic DNA.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…( Previous reports from other countries have shown that MOC has a lower frequency of BRAF mutation (2-20%). [1,2,6] Our data revealed that the BRAF missense mutation rate is relatively up to 80% (n = 16/20) using the FemtoPath BRAF Mutation Screen Kit. This kit is a PCR-based test using proprietary primers which can selectively amplify the somatic mutations in activating segment of the BRAF gene, and suppresses the ampli cation of wild-type BRAF gene in human genomic DNA.…”
Section: Discussionmentioning
confidence: 72%
“…Activating mutations of BRAF can autonomously lead to uncontrolled cellular proliferation and cell survival. The anti-BRAF drugs are successfully used in clinical practice for melanoma and achieve favorable responses for low-grade serous ovarian carcinoma [5,6]. Based on that information, we aimed to explore the BRAF mutation status and evaluate whether it can be a potential therapeutic target for patients with recurrent or advanced stage MOC.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies (such as Wong et al ) using direct Sanger sequencing suggested a better clinical outcome for EOC patients with a BRAF mutation ( 12 ). Preusser et al revealed that patients with invasive carcinomas stained positive for a BRAF V600E monoclonal antibody had a more favorable survival rate ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…BRAF p.V600E, a missense point mutation, is found in approximately 6% of ovarian cancers ( 12 ). Previous studies have shown the BRAF V600E mutation in more than 30% of serous borderline tumors (SBTs), which is associated with low malignant potential (LMP).…”
Section: Introductionmentioning
confidence: 99%
“…In-depth analysis of genetic and histopathological signatures has also led to categorizing OCs into two types, Type I (Low grade) and Type II (High grade). While Type I tumors have a high frequency of KRAS and BRAF mutation, Type II tumors have a high frequency of TP53 mutations [31][32][33][34]. Other biospecimens such as effusions, pap smear fluids, and cervical swabs, are also valuable for understanding OC pathobiology and represent sources of markers that can predict clinical outcomes [35,36].…”
Section: Protein Biomarkers Associated With Ocmentioning
confidence: 99%